Algebra II

posted by .

Solve for x.

log x + log 4x = 2

  • Algebra II -

    log (ab) = log a + log b
    so log 4x = log 4 + log x

    2 log x = 2 - log 4
    log x = (2-log 4)/2

    x = 10^[(2-log 4)/2]

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. TRig WIth LoGs help1!!

    i have problem i can't solve and the book is no help.. anyone got osme hints or somehting i could start off doing?
  2. math

    solve for x without using a calculator 5^(x+1) = 25 i know that x would equal 1 because 5^2 is 25, but i don't know how to show how to solve it All you need to do is what you just did: Explain that if x = 1, the equation is satisfied. …
  3. Algebra 2

    how do not understand how to do this Log X + Lob (X-3) = 1 I know I do this Log X(X-3)=1 then I do this Log X^(2) - 3X = 1 then I do this 2 Log (X-3X) = 1 then 2 Log (-2X) = 1 then (2 Log (-2X) = 1)(1/2) Log (-2X) = 1/2 then (Log (-2X) …
  4. Mathematics

    Prove that log a, log ar, log ar^2 is an a.p. Is the following below correct?
  5. Math Help Please

    Which of the following expressions is equal to log (x sqrt-y)/z^5 A. log x + log (1/2) + log y– log 5 – log z B. log [x + (1/2)y – 5z] C. log x + (1/2)log y – 5 log z d. [(1/2) log x log y]/(5 log z)
  6. math

    Logarithm!!! Select all of the following that are true statements: (a) log(2x) = log(2) + log(x) (b) log(3x) = 3 log(x) (c) log(12y) = 2 log(2) + log(3y) (d) log(5y) = log(20y) – log(4) (e) log(x) = log(5x) – log(5) (f) ln(25) …
  7. college algebra

    Write expression as one logarithm and simplify if appropriate. log 3√x + log x^4 - log x^3 4 log (x+3) - 5 log (x^2+4) + 1/3 log y I have these who problems but I don't know where to start. HELP Please.
  8. Advanced Functions/ Precalculus Log

    1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)x-log(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x-1). …
  9. Math

    h(x) = log (6x+5/7x-4) Find a formula for the inverse function h^-1(x) h^-1(x) = My work so far h(x) = log(6x+5/7x-4) y=log(6x+5/7x-4) x=log(6y+5/7y-4) 7xy-4x= log(6y+5) how would I solve from here. Would I solve for y then do the …
  10. Calculus AB

    How do you solve a system of logarithmic equations?

More Similar Questions